PENGARUH KEMASAN, LABEL HALAL, DAN PENGETAHUAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi pada Konsumen Kosmetik Wardah di Kota Palembang) - Rani Nur Khasanah; Zakaria Wahab; Welly Nailis (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2014)
The purpose of this research is to find out how big the influence of Packaging (X1), Halal Label (X2), and Product Knowledge (X3) On The Purchasing Desicion (Y) and who is a variable that has a dominant influence on purchasing decisions between Packaging, Halal Label, And Product Knowledge (study at consumer of Wardah cosmetic in Palembang city). This research use primary data retreived directly from the respondent through the questionnaire. The number of samples as much as a hundred respondents, sampling technique used is purposive sampling. Analysis technique used in this research is multiple regression analysis, F test and t test. The result obtained show that the magnitude of the influence of variable Packaging (X1), Halal Label (X2), And Product Knowledge (X3) as simultan On The Purchasing Decision (Y) is 58,4 %. The variable that has a dominant influence of the Purchasing Decision is Product Knowledge variable with the value of coefficient of 0,781.Keywords : Packaging, Halal Label, Product Knowledge, Purchasing Decision.